2007
DOI: 10.1590/s0104-42302007000400022
|View full text |Cite
|
Sign up to set email alerts
|

Comparação dos valores de débito cardíaco obtidos por termodiluição e dopplerfluxometria transesofágica

Abstract: INTRODUÇÃOEntre os vários métodos disponíveis para a monitoração do débito cardíaco (DC) de pacientes submetidos a procedimentos cirúrgicos ou internados em unidades de terapia intensiva 1-2 , tem encontrado aceitação universal a termodiluição (TD), considerada gold standard na monitoração hemodinâmica [3][4] . Na última década, diversos estudos foram realizados com o objetivo de encontrar métodos simples e pouco invasivos, que permitam determinar com precisão o débito cardíaco 1,5-6 . Surge assim a dopplerflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In the trained animals, the inhibition of NO synthesis attenuated hypertension, induced cardiac hypertrophy and significantly increased myocardial fibrosis, indicating that NO plays an important role in cardiac tissue adaptations caused by aerobic exercise. Ferreira et al15 found that thermal dilution and trans-esophagic echodoppler yield comparative and reproducible measurements of cardiac output. Menezes Junior et al16 showed that the combined effect of optimized atrial stimulation and atenolol is more effective in controlling recurrent atrial fibrillation.…”
Section: Cardiovascularmentioning
confidence: 99%
“…In the trained animals, the inhibition of NO synthesis attenuated hypertension, induced cardiac hypertrophy and significantly increased myocardial fibrosis, indicating that NO plays an important role in cardiac tissue adaptations caused by aerobic exercise. Ferreira et al15 found that thermal dilution and trans-esophagic echodoppler yield comparative and reproducible measurements of cardiac output. Menezes Junior et al16 showed that the combined effect of optimized atrial stimulation and atenolol is more effective in controlling recurrent atrial fibrillation.…”
Section: Cardiovascularmentioning
confidence: 99%